A educação para a eudaimonia: um estudo sobre os livros VII e VIII da Política de Aristóteles - Felix, Anderson de Araujo (2021)
This dissertation aims to study the conception of Aristotelian education in books VII and VIII of the Politics. Aristotle explains, at the beginning of book VII, that it is only possible to start the discussion about the best political regime if we first answer what is the best life. In fact, the best life is identified with the virtuous life capable of attaining eudaimonia (happiness). Then, he goes on to present the details of this education that aims to reach the highest part of the soul, the rational part, through which it is possible to acquire the necessary virtues for the best life in the city. Therefore, the study of education in Aristotle can clarify aspects of his practical philosophy, notably the theme of the acquisition of virtues and happiness. To understand the details of this education and its implications, we divided this research into three parts that correspond to the three chapters of this dissertation. First, it deals with the meanings of eudaimonia, which will be an introduction to the study of Politics books. Then, it is a question of studying book VII to find the foundation of this education. Finally, it is about studying book VII to understand the scope and the result that the Aristotelian education intends to achieve